2020
DOI: 10.1177/1403494820916093
|View full text |Cite
|
Sign up to set email alerts
|

Women and intimate partner violence: Prevalence of hospital visits and nature of injuries in the Icelandic population

Abstract: Aims: The purpose of this study was to analyse the prevalence of hospital visits and nature of injuries caused by intimate partner violence (IPV) against women and associated costs. Methods: All visits to Landspitali National University Hospital by women 18 years or older subjected to IPV, inflicted by a current or former male partner during 2005–2014, were observed and analysed. Information was obtained on number, date and time of visits and admissions, place of occurrence, patients’ and perpetrators’ age and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
2
9
0
1
Order By: Relevance
“…Our study found that the mean age of respondents who reported being assaulted was 36.57 years. This is similar to another study by Jonasdottir et al20 who reported the mean age of 34 years 20. Our study found the younger women between 26 and 30 years are more vulnerable to violence and the risk decreases with age 20.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study found that the mean age of respondents who reported being assaulted was 36.57 years. This is similar to another study by Jonasdottir et al20 who reported the mean age of 34 years 20. Our study found the younger women between 26 and 30 years are more vulnerable to violence and the risk decreases with age 20.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to another study by Jonasdottir et al 20 who reported the mean age of 34 years. 20 Our study found the younger women between 26 and 30 years are more vulnerable to violence and the risk decreases with age. 20 Our study reported that younger women were more vulnerable to IPV exposure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The obtained results do not allow for a differential diagnosis of the medicolegal aetiology of injuries and intoxications, so no further progress can be made in this discussion. However, superficial injuries are 2.2 times higher (G2) than in the general population, and it is known that they are also most frequent in IPV cases [ 27 , 28 ], which leads us to consider that many of these injuries may have been intentionally inflicted by an intimate partner. Regarding intoxications, they are also two times higher (G2), but here again, the medicolegal aetiology of the cases is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This issue of Scandinavian Journal of Public Health focuses on different aspects of violence against youth and women. An article by Koutaniemi and Einiö describes a novel approach to analysing variations in patterns of information-seeking and police reporting for domestic violence in Finland [9], Jónasdóttir et al report on injuries found in women who sought emergency care in Rejkjavik, Iceland over a 10-year period, 2005–2014 [10] and, in a study from Sweden, Lövestad et al report that women who had experienced physical violence from a partner were several-fold more likely to have mental health care needs, but that nearly half of these had refrained from seeking help [11]. In addition, two articles highlight the health correlates of violence exposure among young people in Sweden; Petersson et al [12] report that youth exposed to any type of violence during their lifetime demonstrated poorer self-rated health than their non-exposed peers, and, in a study by Låftman et al [13], sexual harassment through jokes was found to be highly correlated with psychological complaints among school-aged children.…”
mentioning
confidence: 99%